PENINGKATAN PEMBELAJARAN HORVERSTEHEN III SECARA INTERAKTIF MELALUI PROGRAM MULTIMEDIA-INTERNET - Sulis Triyono (Universitas Negeri Yogyakarta, 2008)
This action research is aimed at (1) improving students 'participation in the class of Horverstehen Ill, (2) improving students' motivation in joining Horverstehen 111, (3) improving students' positive attitudes to study of Horverstehen Ill, and (4) improving students' achievement in Horverstehen III. The subjects are students of the German Departement FBS UNY who take Horverstehen 111 in academic year 200612007. This studyis carried in the Dreamlab. The study consists of two cycles. First cycle, aimed at improving students' attitudes to participate and share activities during the instructional interaction ofHorverstehen III by interactive self-supporting method. Classes are carried out in systematicly, collectively, collaboratively, reflectively, and critically. The second cycle, executed as according to result of first cycle evaluation, and suggestion of student and collaborator. Monitoring and evaluation through observation, questionnaire, and test, which its result used for the reflection of to action. And is hereinafter used to improve; repair insujjiency so that action more success. The result showed that evaluatedfrom process facet, product facet, and value facet. Process facet marked the existence of academic atmosphere, more motivation, and spirit of doing high duties. Productfacet marked by result of work of student in theform of eight duty of Horverstehen which have been sent to lecturer enamel. Valuefacet marked by the existence of more reached score ofstudent offirst duty till eight duty. As for total score which obtained by student is value of A counted 29,41%, value B (47,05%) and also assess C (23,52%)